2016
DOI: 10.1177/1753193416651577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variation in the surgical treatment of patients with distal radial fractures in the Netherlands

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Studies in the US 69,125,126 and in the Netherlands 127 found large regional variation in the incidence of treatment methods for DRFs. After adjusting for factors that possibly influence the choice of surgical method, such as proportion of hand surgeons, academic level of the clinic, age, gender and race, the region remained as a strong predictor for the choice of treatment 125 .…”
Section: Regional Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the US 69,125,126 and in the Netherlands 127 found large regional variation in the incidence of treatment methods for DRFs. After adjusting for factors that possibly influence the choice of surgical method, such as proportion of hand surgeons, academic level of the clinic, age, gender and race, the region remained as a strong predictor for the choice of treatment 125 .…”
Section: Regional Variationmentioning
confidence: 99%
“…Our finding of a large regional variation (adjusted for age and gender) in surgical treatment care of DRFs are supported by several authors. Walenkamp et al 127 reported that operative and non-operative treatment proportions differed largely among regions in the Netherlands. In the US, Fanuele et al 69 and Chung et al 125 found evidence of large regional differences regarding surgical treatment methods as well as surgical rates.…”
Section: Study Imentioning
confidence: 99%
“…Local traditions and personal preferences on behalf of the surgeon largely affect the choice of treatment [ 26 , 27 ]. Large regional variation has been shown to exist in the treatment regimens for distal radius fractures in the US [ 13 , 28 , 29 ] and in the Netherlands [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since it is expected that a preference for certain surgical options may vary according to the healthcare institution type (7), the secondary aim was to examine the surgical trends according to the healthcare institution type.…”
Section: Introductionmentioning
confidence: 99%